The Correlation Between Vocabulary Mastery and Reading Comprehension Among Second-Semester Students of the English Education Department at UIN Mataram - Adhitia Buchori Lalu; Afif Ikhwanul Muslimin; Nurul Lailatul Khusniah; Najamuddin Najamuddin (Program Studi Pendidikan Bahasa Inggris, 2026)
Vocabulary mastery is considered one of the important factors that influence students’ reading comprehension ability. This study aimed to investigate the correlation between vocabulary mastery and reading comprehension among second-semester students of the English Education Department at Islamic State University (UIN) Mataram. This research employed a quantitative correlational design involving 30 students selected through purposive sampling. The data were collected using a vocabulary test and a reading comprehension test. The data were analyzed using SPSS, including descriptive statistics, normality testing with the Shapiro-Wilk test, and Spearman Correlation analysis. The results revealed that the data were not normally distributed; therefore, Spearman Correlation was applied. The analysis showed a significant positive correlation between vocabulary mastery and reading comprehension (r = 0.368, p = 0.045), indicating a weak positive correlation. These findings suggest that students with better vocabulary mastery tend to have better reading comprehension ability. Therefore, vocabulary mastery plays an important role in supporting students’ reading comprehension achievement.